Epidemic Retinitis. (19th May 2019) - Kawali, Ankush; Mahendradas, Padmamalini; Mohan, Ashwin; Mallavarapu, Madhurya; Shetty, Bhujang
ABSTRACT: Purpose : To study demography, seasonal variation, clinical presentation, and treatment outcome of "retinitis post febrile illness." (RpFI) Method : Case records of patients diagnosed as RpFI, from July 2009 to May 2017 were studied retrospectively. Patients with complete follow up were evaluated for treatment and visual outcomes. Results : Two hundred and five eyes of 119 patients were studied. The peak incidence of RpFI was from November to March each year. Diagnosis of fever largely remained unknown. Chikungunya IgM, Dengue IgM, and Weil–Felix test was positive in 22.22%, 15.38%, and 39.75%, respectively, in investigated cases. The mean visual acuity at presentation and at resolution was 20/63 and 20/32, respectively, in 122 eyes with complete follow up. Conclusion : We suggest a term "Epidemic Retinitis" for RpFI due to its seasonal variation and to differentiate it from other sporadic forms of retinitis. Although RpFI has aggressive presentation, it resolves over 3–4 months and the overall visual outcome is satisfactory.